Identifying novel compounds against the mutational impact on the PSEN2 protein via molecular docking studies. (Journal of Pharmaceutical Negative Results, 2022)
Aim.This study aims to identify novel compounds against the mutant structures of PSEN2 protein associated with Alzheimer’s disease by molecular docking studies using molecular docking server. Materials and Methods.In this study, we retrieved the mutant structures of I149T, L238P and R284G mutations of PSEN2 protein from Dynamut, which predicted these mutations to have destabilizing effects on the PSEN2 protein and performed molecular docking with phytochemicals ; Curcumin and Resveratrol using SWISS-DOCK. Results.The docked compounds were analyzed for binding energies. Conclusion.Thus, we have performed molecular docking of mutant structures of the PSEN2 protein with potential phytochemicals using the molecular docking web tool used in our study. These docked compounds may serve as an aid to drug development studies and unravel a potential cure for EOAD.